2020
DOI: 10.1016/j.immuni.2020.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-immune Interactions in the Tissues

Abstract: The ability of the nervous system to sense environmental stimuli and to relay these signals to immune cells via neurotransmitters and neuropeptides is indispensable for effective immunity and tissue homeostasis. Depending on the tissue microenvironment and distinct drivers of a certain immune response, the same neuronal populations and neuro-mediators can exert opposing effects, promoting or inhibiting tissue immunity. Here, we review the current understanding of the mechanisms that underlie the complex intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(117 citation statements)
references
References 97 publications
2
102
0
Order By: Relevance
“…Several neuropeptides and neurotransmitters have been shown to govern immunological functions through discrete subsets of immune cells [228]. SP, a highly conserved neuropeptide that mediates ENS signaling as well as immune cell proliferation and cytokine production, is elevated in IBD and there is evidence of increased numbers of SP-positive neurons in the myenteric plexus of UC patients [229][230][231].…”
Section: Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…Several neuropeptides and neurotransmitters have been shown to govern immunological functions through discrete subsets of immune cells [228]. SP, a highly conserved neuropeptide that mediates ENS signaling as well as immune cell proliferation and cytokine production, is elevated in IBD and there is evidence of increased numbers of SP-positive neurons in the myenteric plexus of UC patients [229][230][231].…”
Section: Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…As a particular subset of primary sensory neurons, nociceptors can respond to pain stimuli and subsequently convert the stimuli into nerve impulses to inform brain to produce the sensation of pain ( 31 ). Once receiving the stimuli, nociceptors can regulate the immune cell response activity at the tissue by releasing neuropeptides which were stored at the dense-core vesicles both in nociceptors’ synaptic terminals at the CNS and in the nerve endings within the peripheral tissues ( 32 ). The transducers of noxious stimuli are voltage-gated and ligand-gated ion channels expressed on the nociceptor nerve terminals, such as transient receptor potential vanilloid subfamily member 1 (TRPV1), transient receptor potential ankyrin 1 (TRPA1), Nav (Voltage-gated sodium channels)1.7, Nav1.8, and Nav1.9 ( 33 ).…”
Section: γδ T Cells Interact With the Peripheral Nervous Systemmentioning
confidence: 99%
“…Most recently, Teratani et al reported the biological mechanism by which bacterial information from the intestinal tract is integrated in the liver and transmitted to the brain to control the production of intestinal regulatory T cells through the vagal nerve reflex [73]. Thus, several experimental approaches have been reported on autonomic innervation of immune organs and neuroimmune modulation [74].…”
Section: Gut Dysbiosis In Agidmentioning
confidence: 99%